Hubungan Bimbingan Orang Tua dengan Prestasi Belajar Siswa - Hasni Kaitotak; Idrus Sere; Ummu Saidah (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2022)
This study aims to determine the relationship between parental guidance and student achievement in PAI subjects in grade VII of SMP Muhammadiyah Ambon. The type of research used is quantitative descriptive, which is research that aims to determine the relationship between parental guidance and student learning achievement in PAI subjects in grade VII of SMP Muhammadiyah Ambon. The sample used in this study was taken randomly amounting to 26 people. The instruments used are tests and questionnaires. Tests are used to determine student achievement and questionnaires are used to determine parental guidance. The data analysis technique used is Product Moment Correlation. The results of the data analysis found that there is a strong relationship between parental guidance and student achievement in Islamic Religious Education subjects in grade VIII of SMP Muhammadiyah Ambon. This is based on the results of the hypothesis test using the product moment correlation test obtained, namely the calculated value obtained of 0.7376. While the conversion results based on the rtabel value distribution table are obtained ttable value which is 0.388.